RECORDING WASTEWATER TREATMENT PLANT OUTLET WATER DISCHARGE USING GOOGLE SHEETS - Zamrowi, Muhammad Wildan; Jamaaluddin (Journal for Technology and Science, 2025)
Objective: The use of IoT-based waste outlet flowmeters is increasingly growing in wastewater monitoring and management. Method: The Method employed in this context is that This technology allows users to monitor the volume and flow rate of waste water in real-time via the internet network. Results: The primary Results obtained are that Its main advantage is in providing accurate and direct data related to actual conditions on the ground, enabling efficient and effective monitoring and better analysis of usage trends. Novelty: Finally, the Novelty of this approach is that Integration with IoT systems also enables the adoption of advanced automation solutions, improving overall operational responsibility, reliability and efficiency.